Effects of monomer functionality on performances of scaffolding morphologic transmission gratings recorded in polymer dispersed liquid crystals. (24th August 2015) - Huang, Wenbin; Pu, Donglin; Shen, Su; Wei, Guojun; Xuan, Li; Chen, Linsen
Abstract: The effects of monomer functionality on performances of holographic polymer dispersed liquid crystal (HPDLC) transmission gratings are systematically investigated. Acrylate monomers with an average functionality ranging from 2.0 to 5.0 are used to prepare these samples. We find scaffolding morphologic transmission gratings (characterized by a high phase separation degree, a well alignment of LCs and low scattering loss) can be obtained irrespective of the monomer functionality, although the exact optimal curing intensity varies. The temporal evolution of the grating formation is studied and the onset time of the LC phase separation decreases significantly with the increase in average monomer functionality. It is also shown that the gratings prepared from low average functionality monomers require a comparatively low switch-off electric field (~8 V  μ m −1 ) whilst suffering from mechanical fragility and long-term instability. Our results not only provide a complete understanding of scaffolding morphologic gratings in terms of the material composition effect, but also provide insight into the formation mechanisms of non-droplet morphologic HPDLC gratings.